Probing the human stereoscopic system with reverse correlation. - Neri, P; Parker, A; Blakemore, C (1999)
Our two eyes obtain slightly different views of the world. The resulting differences in the two retinal images, called binocular disparities, provide us with a stereoscopic sense of depth. The primary visual cortex (V1) contains neurons that are selective for the disparity of individual elements in an image, but this information must be further analysed to complete the stereoscopic process. Here we apply the psychophysical technique of reverse correlation to investigate disparity processing in human vision. Observers viewed binocular random-dot patterns, with 'signal' dots in a specific depth plane plus 'noise' dots with randomly assigned disparities. By examining the correlation between the observers' ability to detect the plane and the particular sample of 'noise' disparities presented on each trial, we revealed detection 'filters', whose disparity selectivity was remarkably similar to that of individual neurons in monkey V1. Moreover, if the noise dots were of opposite contrast in the two eyes, the tuning inverted, just like the response patterns of V1 neurons. Reverse correlation appears to probe disparity processing at the earliest stages of binocular combination, prior to the generation of a full stereoscopic depth percept.